ATTACHMENT IN THE TEACHER-STUDENT DYAD AND GENDER ROLES - Matric, Maja (Journal of process management and new technologies, 2019)
Attachment theory offers an exceptional insight into the individual’s personality, since it can be used to explain his or her behaviour and cognitive patterns present in everyday interactions with people in domestic, educational or professional spheres. An overview of the literature helps us study early childhood attachment relationships, which consequently influence relationships formed later in life – here, the focus is on elementary education period, where attachment is used to look into the student-teacher relationship. Taking into account gender when exploring attachment relationships in the early childhood, as well as traditional notions of gender roles, we raise the question whether these are indeed elements defining the quality of a child’s attachment relationship to a female or male teacher and propose a research plan.